2021
DOI: 10.1007/s11102-021-01167-y
|View full text |Cite
|
Sign up to set email alerts
|

Complication avoidance protocols in endoscopic pituitary adenoma surgery: a retrospective cohort study in 514 patients

Abstract: Purpose To evaluate the impact of using consistent complication-avoidance protocols in patients undergoing endoscopic pituitary adenoma surgery including techniques for avoiding anosmia, epistaxis, carotid artery injury, hypopituitarism, cerebrospinal fluid leaks and meningitis. Methods All patients undergoing endoscopic adenoma resection from 2010 to 2020 were included. Primary outcomes included 90-day complication rates, gland function outcomes, reoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 66 publications
(131 reference statements)
1
8
0
Order By: Relevance
“…Readmission within 30-days of discharge after EETS is an important topic due to patient care and cost considerations, especially with the recent trend towards rapid discharge after EETS. Several studies have commented on readmission rates and causes, with readmission occurring in 4.6-13.9% of patients, most commonly due to hyponatremia [20][21][22][23][24][25][26][27]. Our ndings are similar with 9.5% of all patients in our cohort requiring readmission within 30 days of surgery, and 34.5% of readmissions being secondary to hyponatremia.…”
Section: Extent Of Resectionsupporting
confidence: 80%
“…Readmission within 30-days of discharge after EETS is an important topic due to patient care and cost considerations, especially with the recent trend towards rapid discharge after EETS. Several studies have commented on readmission rates and causes, with readmission occurring in 4.6-13.9% of patients, most commonly due to hyponatremia [20][21][22][23][24][25][26][27]. Our ndings are similar with 9.5% of all patients in our cohort requiring readmission within 30 days of surgery, and 34.5% of readmissions being secondary to hyponatremia.…”
Section: Extent Of Resectionsupporting
confidence: 80%
“…However, our surgical complications were higher than the recent reports from experienced pituitary centers. (12,19) This could be related to the lower numbers of patients in our study and our less surgical experience. Nevertheless, the tumors in our series were slightly large, potentially causing complications, especially when GTR was attempted.…”
Section: Discussionmentioning
confidence: 80%
“…The rate of GTR in this study was comparable with the recent studies ranging from 57.6% to 95.4%. (11)(12)(13)(14). Although previous studies comparing surgical outcomes in ETSA and MTSA have shown inconsistent results, meta-analyses and systematic reviews in recent years have found generally favored ETSA.…”
Section: Discussionmentioning
confidence: 99%
“…25 Simulation training can also help generate checklists for best practices (e.g., carotid injury on an endonasal procedure, management of cerebrospinal fluid leak). [26][27][28]…”
Section: Future Directionsmentioning
confidence: 99%
“…25 Simulation training can also help generate checklists for best practices (e.g., carotid injury on an endonasal procedure, management of cerebrospinal fluid leak). [26][27][28] Plans to continue expanding RAPID to other topics and institutional sites have been proposed. Additional topics will require involvement and agreement from different clinical sites.…”
Section: Future Directionsmentioning
confidence: 99%